Busting silos - Carpio, Hillary; Henry, Travis (Ascent Audio, 2023)
Unify your teams and go to market like the best in the business Hillary Carpio and Travis Henry of Snowflake helped scale the go-to market program behind one of the fastest growing software companies in history. Not satisfied with the traditional model of separate sales and marketing functions, they married both into integrated, account-based, cross-functional teams that targeted and closed business at historic rates-what they call "one-team GTM." In Busting Silos: How Snowflake Unites Sales and Marketing to Win Its Best Customers, Carpio and Henry map out how you can do the same at scale. Learn to: turn your funnel upside down and stop wasting resources; design a one-team ABM program, align people with strategy, and win buy-in; deliver the right message at the right time to the right account; and scale your pilot to sell (and upsell) to enterprise heights. Whether you are building a new ABM function or scaling an existing one, your ABM and sales development reps are likely siloed. To go to market at size, speed, and scale like Snowflake, that needs to change. Busting Silos is your roadmap to making it happen
Online resource; title from title details screen (O'Reilly, viewed July 11, 2023)
Keywords: Industrial marketing -- Management; Selling -- Key accounts; Marketing -- Key accounts; Consumers -- Management; Relationship marketing; Marketing industriel; Gestion; Budgets de publicité; Marketing relationnel; Industrial marketing; Management; Marketing; Key accounts; Selling; Key accounts; Audiobooks; Livres audio